Penerapan Model Pembelajaran Cooperative Learning Tipe Team Games Tournament (TGT) Untuk Meningkatkan Keterampilan Berpikir Kritis Pembelajaran IPS Peserta Didik Kelas V Sekolah Dasar - Fahrizal, Mochammad (Universitas Sebelas Maret, 2020)
Abstract: The purpose of this research is to improve the critical thinking skills of social science lessons using the TGT (Team Games Tournment) type of cooperative learning model. The research conducted was classroom action research. This research was conducted in two cycles and in each cycle two meetings were held. The subjects of this study were students of grade SDN Karangsem 1 Ssurkarta with a total of 33 students. Data collection techniques used in this study were observation, interviews, documentation and tests. The data analysis technique used in this study refers to the Miles-Huberman data analysis technique. The results of the study in the first cycle showed the percentage of students completeness of 30%, and the study continued in the second cycle which showed a percentage of students completeness of 77%. This proves that the application of the TGT type of cooperative learning model can improve the critical thinking skills of 5th grade students at SDN Karangasem 1 Surakarta.